Role of Lumbar Puncture for First Simple Febrile Seizure Among Children 6 to 18 Months of Age - Haque, M Sanaul; Yeasmin, Shahida; Dutta, Poly; Kumar, PK Chandan; Kundu, Pijush Kumar (TAJ: Journal of Teachers Association, 2018)
Introduction: Fever with seizure is a common childhood emergency. This may be due to febrile seizure or CNS infection like meningitis. Febrile seizure makes up the most common convulsive event in children 6 months to 5 years of age. Despite the commonness of this clinical problem, the need for routine lumbar puncture following a first simple febrile seizure below 18 months of age to exclude meningitis continues to be debated. Objectives: To evaluate the role of lumbar puncture for first simple febrile seizure among children 6 to 18 months of age and to determine the causes of fever of the patient presented with fever with simple seizure in this age group. Methodology: This cross-sectional type of descriptive study was conducted at Paediatric department of Rajshahi Medical College from January 2013 to December 2014.A total of 73 children ages 6 months to 18 months with first simple febrile seizure were enrolled by purposive sampling technique. Lumbar puncture was performed in all patients to evaluate occult meningitis. Results: A total of 73 children ages 6 months to 18 months with first simple febrile seizure were included in the study. 37% (n = 27) were < 12 months of age and 63% (n = 46) were ≥12 months of age with a mean age 13±3.575 months. 43.8% of our study population had family history of febrile seizure. CSF findings of all children > 12 months of age group 63% (n = 46) were normal but in case of age group <12 months, out of 37% (n = 27) cases, only one case showed abnormal CSF finding. Conclusion: It is concluded that lumbar puncture following first simple febrile seizure without any other features of meningitis may be done in children < 12 months of age. TAJ 2011; 24(2): 65-69